Talocalcaneal coalition resection and bone block subtalar joint arthrodesis: a techinical tip - Iehl, Caleb; Auch, Elijah; Vivtcharenko, Victoria; Mansur, Nacime Salomão Barbachan; Kowalski, Heather; de Cesar Netto, Cesar de (Journal of the Foot & Ankle, 2020)
In this technical tip, we present the case of an obese 17-year-old female diagnosed with a severe, rigid, and symptomatic flatfoot on a background of exuberant talocalcaneal and residual calcaneonavicular coalition. Through a technical modification of the fusion resection, both coalitions were quickly and safely removed with two single cuts of an oscillating saw, resecting a medial wedge through a medial approach, without the need for “peel-off” tarsal coalition resection. To protect and guide the resection osteotomy, one Freer elevator ws inserted under direct visualization on the patent posterolateral aspect of the subtalar joint posterior facet and a second elevator was positioned underneath the talar neck. Under fluoroscopic guidance, an osteotomy was performed connecting these two points. The patient also received a bone-block subtalar joint arthrodesis and a Cotton osteotomy. Good short-term alignment correction and functional outcome were achieved. Level of Evidence V; Therapeutic Studies; Expert Opinion.